REPRODUCTIVE POTENTIAL OF POTATO ACCESSIONS FROM THE VIR COLLECTION IN MURMANSK PROVINCE - S. N. Travina; Т. Е. Zhigadlo (Труды по прикладной ботанике, генетике и селекции)
Background. Knowledge of the reproductive potential in plants is of vital importance for potato cultivation in the Arctic environments.Materials and methods. From 2008 through 2017, 1594 potato cultivars with diverse maturation schedules from VIR’s collection were studied at the Polar Experiment Station of VIR. The material was evaluated according to the timing of their phenological phases (germination, budding, and flowering) and the possibility of their reproductive organs’ development.Results: With the same agricultural practice applied, cultivars of different maturation groups began to germinate and produce shoots at about the same time within the growing season, with a slight difference from 0.2 days (2010) to 3.3 days (2015). Further passing of phenological phases under the conditions of the Arctic depended on the mean daily air temperature and precipitation. The duration of the period from germination to flowering was largely affected by the temperature regime. The emergence of mass shoots was observed on average 18.5 ± 2.9 days after planting. The budding phase started 31.9 ± 4.7 to 43.0 ± 6.9 days after planting. The beginning of flowering occurred at the beginning of the third decade of July or 46.8 ± 4.9 to 57.5 ± 7.5 days after planting. The duration of the mass flowering of potato plants on average covered the time frame from the end of July to the middle of the third ten-day period of August. To move a potato plant from the budding phase to the flowering/mass flowering phase, a sum of effective July temperatures of 300°C is required. During the growing season, for all the years of the study, 97% of the varieties, as related to the total number of accessions, were able to set up buds; 85.7% entered the flowering stage; 63.3% moved to the stage of mass flowering; and 22.2% were able to set berries from self-pollination. According to the data of the long-term analysis of perennial agrometeorological data, the most favorable conditions for setting berries after potato self-pollination recurred every five years in the north. These conditions were formed under the sum of active air temperatures from 1170 to 1300°С (for June, July, and August), combined with insufficient provision of precipitation. Under the natural conditions in the north, the lack of moisture stimulates plants to enter the stages of flowering and fruit setting quicker and more intensively.Conclusion: The study made it possible to identify the optimal conditions for the fruit to be set by a potato plant in the north and also to acquire more data on the reproduction characteristics of potato cultivars.